Development of a Supervisory Skills Course for Hospital Pharmacy Workplaces - Woloschuk, Donna M M (Canadian Society of Hospital Pharmacists, 2010)
BACKGROUND AND OBJECTIVE: Many Canadian hospital pharmacies are experiencing difficulties recruiting supervisory personnel. It was expected that, through a “learning-by-doing” course, pharmacy staff would learn to apply basic skills in the day-to-day supervision of pharmacy operations and human resources and to apply the principles of supervisory documentation. METHODS: A supervisory skills course targeted to pharmacy staff members was developed and implemented by the pharmacy department of a large urban health region. The course was initially offered to practising pharmacy technicians. The course design emphasized a constructivist framework incorporating authentic learning and reflective practice during seminars, with experiential and self-directed learning in the workplace. Preceptors assisted learners to achieve the course goals. Learners and preceptors provided feedback about hours spent (as the course progressed) and about their satisfaction with the course itself (at the end of the course). Learners and preceptors completed a post-program evaluation 2 months after completing the course to help in the assessment of the transfer of learning (lasting impact) associated with the course. Overall performance in the course was assessed on a pass/fail basis. RESULTS: Eighteen pharmacy technicians were admitted to the program, but one withdrew because of a job change. All learners successfully completed the course. Two months after the course, learners and preceptors described enhanced organization, time management, leadership, communication, and conflict-resolution skills on the part of learners, as well as their increased confidence, maturity, and ability to supervise staff. Learners’ evaluations revealed a broadened perspective of pharmacy. The preceptors valued the enhancement of learners’ skills and their increased enthusiasm. At the time of writing, 6 of the participants had secured supervisory positions. CONCLUSION: Creating formal instruction that engages pharmacy staff to pursue management positions is challenging. Instructional design grounded in constructivist theory and incorporating authentic learning experiences and reflection resulted in high learner satisfaction with learning outcomes.